Evaluation of the Bundo Kanduang Institute in Nagari Balai Panjang, Lareh Sago Halaban District - Khairat, Annisaul; Fuaddin, Iskandar (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Minangkabau customary institutions have strong sociological and psychological ties with the surrounding environment. Women are the driving force behind the Bundo Kanduang institution, which deals with issues concerning women, children and the household. But usually the problem that arises is the authority of women to carry out activities outside the home. The aim of this research is to strengthen the Bundo Kanduang institution in the nagari and promote development. In the context of implementing bundo kanduang activities in Nagari Balai Panjang, Lareh Sago, Halaban Regency, this study aims to determine (1) community participation and needs for bundo kanduang institutions (2) motivation, participant characteristics, and resources, funds, facilities, and infrastructure . The data collection in this study, using a descriptive methodology with a qualitative approach. The data collection techniques that is used were observation, interviews, documentation, and written sources. The findings of this study indicate that (1) the community supports the existence of the bundo kanduang institution; (2) the motivation and enthusiasm of the participants is relatively strong, and the implementation of the activities causes changes in the attitudes of the participants, including their technical and social skills.